Effects of corrective surgery on social phobia, psychological distress, disease-related disability and quality of life in adult strabismus patients - (:unkn) unknown (BMJ PUBLISHING GROUP, 2014)
Background Corrective surgery is done for ocular alignment and disrupted facial expression in some cases of adult strabismus patients. The effects of corrective surgery on the presence of social phobia (SP) diagnosis, the severity of social anxiety symptoms, the disease-related disability and the quality of life (QoL) among strabismus patients have not been thoroughly studied yet. Methods The study sample was composed of patients who had undergone corrective surgery for strabismus. Preoperative and postoperative evaluations made by using standardised measures of social phobia diagnosis (DSM-IV-TR) and severity (Liebowitz Social Anxiety Scale (LSAS)), anxiety and depression (Hospital Anxiety and Depression Scale (HADS)), disability (Sheehan Disability Scale) and quality of life (short form-36). Results Preoperatively, SP diagnosis was detected in 17 of 31 (54.8%) patients, whereas postoperatively 6 of 31 (19.4%) patients had SP (p=0.001). Participants showed a significant decrease in all subscale scores and total score of both LSAS and HADS compared with their preoperative scores. Significant improvements were observed in QoL and disability scores as well. Conclusions Adult strabismus patients seem to gain benefits from corrective surgery not only for their ocular misalignment but also for social anxiety levels that may be associated with improvements in their QoL and disability levels.
Keywords: PSYCHOSOCIAL-ASPECTS; ESSENTIAL TREMOR; IMPACT; MANAGEMENT; BENEFITS